Effects of maternal abdominal decompression on umbilical artery and fetal middle cerebral artery blood flow - Sara Mugerli; Gordana Njenjić; Vesna Fabjan Vodušek; Miha Lučovnik (Nurses and Midwives Association of Slovenia, 2015)
Introduction: Maternal abdominal decompression during pregnancy could be used in an attempt to improve utero-placental blood flow. We utilized Doppler ultrasonography to investigate the effects of this procedure on blood flow in the umbilical artery and fetal middle cerebral artery. Methods: Women (n = 23) with singleton pregnancies attending antenatal abdominal decompression were enrolled in the study. Doppler velocity waveforms were obtained from umbilical artery and fetal middle cerebral artery before and after a 30-minute decompression session. Resistance indices were compared using the Student's t - test (p < 0.05 significant). Results: 23 healthy pregnant women were included at an average gestational age of 36+1 weeks. The mean resistance index before decompression in the umbilical artery was 0.58 (s = 0.10) and after decompression 0.54 (s = 0.07, p = 0.06). In the middle cerebral artery the values were 0.72 (s = 0.11) and 0.77 (s = 0.08), respectively (p = 0.01). Discussion and conclusion: Significantly increased resistance index in the middle cerebral artery implies a higher fetal brain oxygenation after decompression. This is further corroborated by the trend towards a decrease in umbilical artery resistance index. The effects of decompression could be beneficial in pregnancies complicated by IUGR or hypertensive disorders of pregnancy.